The 19th-century missionary encounters with the Batswana people in South Africa: An intersectional-decolonial approach - Shingange, Themba (Verbum et ecclesia, 2024)
Missionary encounters were often characterised by shifting and multilinear intents within the broader global spaces. In Africa, the 19th-century missionary encounter happened concomitantly within the nexus of Christianisation, colonisation, and civilisation agendas. Succinctly put, missionaries sent by the London Missionary Society who came to South Africa and had encounters with the Batswana people were equally agents of cultural transfer and imperialism that were linked to Christianisation, colonisation, and civilisation processes. Thus, the missionary mandate was entrenched in evangelisation that constructed and portrayed to Africans the imagery of a monotheistic and monopolistic God, and in the deformation and classification of African cultural practices and religions as heathen, barbaric, and uncivilised. Consequently, the dividing line between Christianisation, colonisation, and civilisation was blurred. This study used desk research to examine the nexus of missionary encounters among the Batswana in South Africa. The findings were that the understanding of Christianity and the imagery of God depicted by the missionaries still has a grip on contemporary Africa. Therefore, there is a dire need to problematise the narrative because it has continued the colonial aspirations of the past.Intradisciplinary and/or interdisciplinary implicationsThe study used intradisciplinary and interdisciplinary approaches by engaging the intersectional and decolonial theories together with insights from theology and missiology. This was done to delineate the problem and to argue for the need to decolonise the current narrative. This can, perhaps, transform the status quo and provide opportunities for Africans to define their beings and understanding of God in their terms.